Analisis Penerapan Breastfeeding Peer Counseling Pada Pasien Post Partum Fisiologis Dengan Masalah Keperawatan Menyusui Tidak Efektif Berdasarkan Teori Maternal Role Attainment-Becoming A Mother Ramona T. Mercer - Dwi Rahayu; Yunarsih Yunarsih (coba, 2015)
The postpartum period is a critical time for the mother of one side is happy at the same times stressful to adapt after childbirth. Adaptation includes adjusting to build a positive interaction with the baby. One of the problems that occur in the postpartum period is the failure of mothers in exclusive breastfeeding. The low exclusive breastfeeding for mothers because they do not know the benefits of breastfeeding for children's health. Support from father also affect the success of exclusive breastfeeding for six months. Mother's decision to breastfeed affected family members information about the benefits of breastfeeding, as well as a lactation consultant. The purpose of this study is to analyze specific interventions , namely breastfeeding peer Counseling to improve exclusive breastfeeding in the postpartum period using theory of nursing, Maternal Role Attainment - Becoming a Mother developed by Ramona T. Mercer. The method used in this paper is a case report on the Physiological Postpartum Mothers treated in Kabupaten Kediri Hospital. On The assessment results according to the theory of Ramona T Mercer in the antisipatori data obtained on the condition of pregnancy that the mother does not experience problems, the ANC program appropriate with the schedule of health workers. In the Formal assessment of the phase Formal acceptance by the baby's mother obtained the difficulty breast-feeding mother to baby and family support is still lacking. In the Informal phase obtained for fear the baby's mother in the care especially during the current bathing and cord care. In the personal phase obtained mother feel mother’s role is very important in baby care. Breastfeeding Peer Counseling can be applied to postpartum mothers who experience difficulties with breastfeeding to their babies. The program is to motivate mothers to give babies the best nutrition to their infants through exclusive breastfeeding and provide psychological support to the mother to perform maintenance on the baby independently.